18 Is my ACLR strong enough? Graft type, activity level influence knee strength in 392 athletes across five time points. (25th January 2023) - Korakakis, Vasileios; Kotsifaki, Roula; Whiteley, Rod
Abstract : Introduction: An essential priority in rehabilitation after anterior cruciate ligament reconstruction (ACLR) is the restoration of knee muscle strength. We aimed to describe quadriceps and hamstrings strength after ACLR of an uncomplicated rehabilitation course, categorized into level of activity and graft type (patellar-tendon – BPTBG, hamstring – HSG). Methods: Isokinetic concentric strength (body weight – BW-adjusted) was measured in 392 athletes (26.2±6.7y) at five time-points (3, 4.5, 6, 7.5, and 9m) following ACLR. Data was analyzed using mixed-effects models and participant specific random effects. Fixed effects included graft type, athlete categorization, and assessment time. We applied Tukey adjustment for multiple comparisons. Results: Professional athletes (HSG) displayed greater quadriceps strength than recreational (BPTBG) at all time-points (except 7.5m). No other significant differences were noted. Professional and recreational athletes' quadriceps strength significantly increased through time (irrespective of graft type). Professionals (HSG) reached >2.5 BW quadriceps strength at 6-months, and recreationals >2.3 BW at 7.5-months. Professional athletes showed significantly greater hamstring strength through time (irrespective of graft type). Both athletic categories reached maximum hamstring strength at 6-months post operatively (>1.7 BPTB and >1.5 HS, BW). Recreational athletes (BPTBG) displayed a significant increase in hamstring strength (1.4 BW, 4.5m), while for recreational athletes (HSG) strength was consistently improving up to 7.5m. Conclusions: Knee strength increases during rehabilitation but at the initial phase of ACLR rehabilitation is influenced by the graft type, while at the end of rehabilitation it is affected by the activity level. The maximum achieved strength is affected mostly by activity level.